2017
DOI: 10.1177/0954410017711722
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and control of underactuated spacecraft formation reconfiguration in elliptic orbits

Abstract: Feasibility of underactuated formation reconfiguration in elliptic orbits without radial or in-track thrust is investigated in this paper. For either underactuated case, by using a linear time-varying dynamical model of spacecraft formation, controllability and feasibility analyses are conducted, based on which the preconditions on reconfigurable formations are then derived. With the inherent coupling of system dynamics, the reduced-order sliding mode control technique is employed to design a closed-loop under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…2) New underactuated control schemes that decouple the radial and along-track system states are presented for spacecraft formation reconfiguration without either the radial or the along-track control. Notably, the Lyapunov-based approach proves that the bounded convergence regions of system states in this work are less than those in Huang et al 27,28 3) To address the challenges posed by thrust loss, timevarying system coefficients, and input saturation, the underactuated saturation controllers are developed for either underactuated case. Especially for the case without along-track thrust, the timeinvariant and time-varying coefficients of the system in the controller satisfy the same linear transformation.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…2) New underactuated control schemes that decouple the radial and along-track system states are presented for spacecraft formation reconfiguration without either the radial or the along-track control. Notably, the Lyapunov-based approach proves that the bounded convergence regions of system states in this work are less than those in Huang et al 27,28 3) To address the challenges posed by thrust loss, timevarying system coefficients, and input saturation, the underactuated saturation controllers are developed for either underactuated case. Especially for the case without along-track thrust, the timeinvariant and time-varying coefficients of the system in the controller satisfy the same linear transformation.…”
Section: Introductionmentioning
confidence: 89%
“…is nonsingular, where t 0 and t f are the initial and terminal times, respectively. By using Lemma 2, Huang et al 27 concluded the controllability analysis of underactuated formation flying in elliptic orbits: the system is controllable for the case without radial control but uncontrollable in the absence of along-track control. Note that the controllability decomposition approach is based on the rank criterion theory, which can only analyze the controllability of a linear time-invariant system.…”
Section: Controllability and Feasibility Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…There are some studies investigating non-radial thrust in the orbital-transfer problem. 1315 More recently, Quarta and Mengali 16 proposed a new formulation to reassess the classical circumferential-thrust problem, assuming the propulsive acceleration modulus to be sufficiently small to reduce the mathematical complexity of the problem. In 2019, the same research group investigated the optimal-transfer trajectories from a circular parking orbit toward the apocenter of a rectilinear ellipse, for a spacecraft equipped with a burning system that provides a circumferential continuous propulsive acceleration.…”
Section: Introductionmentioning
confidence: 99%